The Decline of the Umayyad Caliphate in Andalus Based on Ibn Khaldun’s Theory - Abdullah, Suhaila; Mohd Talib, Nurliyana (Journal of Al-Tamaddun, 2023)
This inquiry examines the downfall of the Umayyad Caliphate in Cordoba, Andalus (Spain), in 1031 CE, which signaled the end of almost three centuries of Umayyad dominance in the region under Islamic governance. The primary objective of this study is to scrutinize the factors contributing to the demise of the Umayyad Caliphate in Andalus, drawing upon the insights presented by Ibn Khaldun. Employing a qualitative research approach, the study utilized content analysis methodology to examine pertinent documents and additional written sources. The findings of this research, as per Ibn Khaldun’s theories, identified critical elements that precipitated the collapse of the Umayyad government. These included a failed state, political disintegration, severe financial crises stemming from the erosion of social solidarity, a decline in the sense of belonging (‘asabiyyah), instances of injustice and tyranny, a culture of opulence, and weakened religious adherence. Ultimately, the populace of Andalus withdrew their support for the Umayyad Caliphate, leading to a diminishing sense of social solidarity. Consequently, the Islamic civilization in Andalus underwent a gradual decline, culminating in its destruction by external forces.